(untitled) (Bangladesh Agronomy Journal, 2016)
An experiment was conducted during T. Aman season, 2014 at the Agronomy Research Field, Bangladesh Rice Research Institute, Gazipur to determine the optimum rate of nitrogen fertilizer for higher yield in nerica rice. The experiment comprised of three rice varieties viz. NERICA1, NERICA10 and BRRI dhan57; and five nitrogen levels viz. 0, 23, 46, 69 and 92 kg ha-1. The rice var. BRRI dhan57 with 69 and 92 kg N ha-1 produced significantly identical with higher panicles m-2. But NERICA1 and NERICA10 produced higher number of panicles with 46 and 69 kg N ha-1, respectively. However, BRRI dhan57 with 46 kg N ha-1 produced highest grains panicle-1 but NERICA1 and NERICA10 produced higher number of grains panicle-1 with 23 kg N ha-1. The highest percentage of sterility was recorded in NERICA10 with 69 kg N ha-1. The regression analysis gave the optimum dose of nitrogen for NERICA1, NERICA10 and BRRI dhan57 which were 69.25, 74.25 and 85.75 kg N ha-1, respectively. Bangladesh Agron. J. 2015, 18(2): 9-14